2008
DOI: 10.1016/j.freeradbiomed.2008.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Self-regulatory role of 4-hydroxynonenal in signaling for stress-induced programmed cell death

Abstract: Within the last two decades, 4-hydroxynonenal has emerged as an important second messenger involved in the regulation of various cellular processes. Our recent studies suggest that HNE can induce apoptosis in various cells through the death receptor Fas (CD95)-mediated extrinsic pathway as well as through the p53-dependent intrinsic pathway. Interestingly, through its interaction with the nuclear protein Daxx, HNE can self-limit its apoptotic role by translocating Daxx to cytoplasm where it binds to Fas and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(108 citation statements)
references
References 115 publications
(188 reference statements)
7
101
0
Order By: Relevance
“…The latter, in turn, might foster cell damage via the release of ferrous ions, ROS and cathepsins, cytosolic amplification of LPO, aldehyde-mediated protein/DNA modification and mitochondrial outer membrane permeabilization, leading to Fas-and p53-mediated apoptosis or necrosis, depending on the severity of oxidative stress (19). HNE itself was able to trigger p53 and Fas-dependent apoptosis (11). The conclusions drawn in the study cited (19) had some limitations, in that: a) HNE-His-P immunoreactivity (71).…”
Section: Hne-protein Adducts In Chronic Inflammatory Diseasesmentioning
confidence: 99%
“…The latter, in turn, might foster cell damage via the release of ferrous ions, ROS and cathepsins, cytosolic amplification of LPO, aldehyde-mediated protein/DNA modification and mitochondrial outer membrane permeabilization, leading to Fas-and p53-mediated apoptosis or necrosis, depending on the severity of oxidative stress (19). HNE itself was able to trigger p53 and Fas-dependent apoptosis (11). The conclusions drawn in the study cited (19) had some limitations, in that: a) HNE-His-P immunoreactivity (71).…”
Section: Hne-protein Adducts In Chronic Inflammatory Diseasesmentioning
confidence: 99%
“…From the viewpoint of production of free radicals, ROS/RNS can attack and damage a variety of critical biological molecules, including lipids, essential cellular proteins and DNA [9][10][11] . Products of lipid peroxidation can be easily detected in biological fluids and tissues and can reliably and rapidly reflect the sensitive and specific signals of lipid peroxidation that occur in vivo [35,36] . The compound 4-HNE is an end product of lipoperoxidation with antiproliferative and proapoptotic properties [35,36] .…”
Section: Discussionmentioning
confidence: 99%
“…Products of lipid peroxidation can be easily detected in biological fluids and tissues and can reliably and rapidly reflect the sensitive and specific signals of lipid peroxidation that occur in vivo [35,36] . The compound 4-HNE is an end product of lipoperoxidation with antiproliferative and proapoptotic properties [35,36] . Our results with MDA and 4-HNE confirmed that OS occurred even in the early postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Such compounds have been amply documented to alkylate particular protein thiols under oxidative or nitrosative stress and therefore may be implicated as stress signaling molecules that are sensed via S-alkylation. The best known example of a regulatory protein modified this way is kelch-like ECH-associated protein-1 (Keap1), which plays a pivotal role in responding to oxidative challenge with an adaptive response via activation of the transcription factor Nrf2 (6, 94-98, 254, 479, 481) (see section III), but analogous stress sensing has also been implicated in the NF-jB pathway (408) and in apoptosis (12).…”
Section: Signals Of Free Radical Damagementioning
confidence: 99%